Jews and Humor - Greenspoon, Leonard J. (Leonard Jay); University of Nebraska--Lincoln. Harris Center for Judaic Studies; Philip M. and Ethel Klutznick Chair in Jewish Civilization; Klutznick-Harris Symposium 2009 : Omaha, Neb.); Project Muse. (West Lafayette, Indiana : Purdue University Press, 2011)
"Jews and humor is, for most people, a natural and felicitous collocation. In spite of, or perhaps because of, a history of crises and living on the edge, Jews have often created or resorted to humor. But what is "humor"? And what makes certain types, instances, or performances of humor "Jewish"? These are among the myriad queries addressed by the fourteen authors whose essays are collected in this volume. And, thankfully, their observations, always apt and often witty, are expressed with a lightness of style and a depth of analysis that are appropriate to the many topics they cover. The chronological range of these essays is vast: from the Hebrew Bible to the 2000s, with many stops in between for Talmudic texts, medieval parodies, eighteenth century joke books, and twentieth century popular entertainment.The subject matter is equally impressive.In addition to rounding up many of the "usual suspects," such as Woody Allen, the Marx Brothers, and Gilda Radner, these authors also scout out some unlikely comic resources, like the author of the biblical book of Exodus, the rabbinic writer of Genesis Rabbah, and the party records star Belle Barth. Without forcing any of these characters into a pre-constructed mold, the scholars who contributed to this collection allow readers both to discern the common features that make up "Jewish humor" and to delight in the individualism and eccentricities of the many figures whose lives and accomplishments are narrated here. Because these essays are written in a clear, jargon-free style, they will appeal to everyone-even those who don't usually crack a smile!" -- P. [4] of cover.
Humor in the Bible / Charles David Isbell -- Why did the widow have a goat in her bed? : Jewish humor and its roots in the Talmud and Midrash / David Brodsky -- But is it funny? : identifying humor, satire, and parody in rabbinic literature / Eliezer Diamond -- Masekhet Purim / Peter J. Haas -- Jewish humor as a source of research on Polish-Jewish relations / Joanna Sliwa -- Jewish jokes, Yiddish storytelling, and Sholem Aleichem : a discursive approach / Jordan Finkin -- Groucho, Harpo, Chico, and Karl : immigrant humor and the Depression / Leonard M. Helfgott -- Nuances and subtleties in Jewish film humor / Michael W. Rubinoff -- The bad girls of Jewish comedy : gender, class, assimilation, and whiteness in Postwar America / Giovanna P. Del Negro -- One clove away from a pomander ball : the subversive tradition of Jewish female comedians / Joyce Antler -- Heckling the divine : Woody Allen, the Book of Job, and Jewish theology after the Holocaust / Jason Kalman -- Tragicomedy and zikkaron in Mel Brooks's "To be or not to be" / Joan Latchaw and David Peterson -- "They ain't makin' Jews like Jesus anymore" : the musical humor of Kinky Friedman and the Texas Jewboys in historical and geographical perspective / Theodore Albrecht -- The new Jewish blackface : African American tropes in contemporary Jewish humor / David Gillota.
"Proceedings of the twenty-second annual symposium of the Klutznick Chair in Jewish Civilization - Harris Center for Judaic Studies, October 25-26, 2009" -- P. [i].
Includes bibliographical references.
Description based on print version record.
Keywords: Jews -- Humor -- History and criticism; Jewish wit and humor -- History and criticism; Electronic books